2021
DOI: 10.48550/arxiv.2106.10909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Channel Estimation for Hybrid RIS Aided MIMO Communications via Atomic Norm Minimization

Abstract: Reconfigurable intelligent surfaces (RISs) have been introduced as a remedy for mitigating frequent blockages in millimeter wave (mmWave) multiple-input multiple-output (MIMO) communication networks. However, perfect or nearly perfect channel state information (CSI) is fundamental in order to achieve their full potential. Traditionally, an RIS is fully passive without any baseband processing capabilities, which poses great challenges for CSI acquisition. Thus, we focus on the hybrid RIS architecture, where a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, SE changes with respect to the RIS location. In [52] and [55], it was observed that better SE performance was obtained when RIS was closer to BS.…”
Section: A Traditional Estimation Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, SE changes with respect to the RIS location. In [52] and [55], it was observed that better SE performance was obtained when RIS was closer to BS.…”
Section: A Traditional Estimation Techniquesmentioning
confidence: 98%
“…The authors in [55] considered uplink RIS with a certain number of active sensors, where users send pilot signals to BS via RIS. This work aimed to recover the BS-RIS channel pa-rameters and extract the RIS-BS channel characteristics from the obtained signal.…”
Section: A Traditional Estimation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are essentially normal reflective antenna arrays without the base band or RF units. These structures are often considered to be fully passive besides some semi-passive structures where certain set of elements receive and help with the channel estimation [21]. The antenna array type approach allows individual phase control at each antenna.…”
Section: Ris Modelingmentioning
confidence: 99%
“…The former allows the CE to be formulated as a sparserecovery problem and solved using compressed sensing (CS) tools [10]- [12], which are known to require a few measurements to have an accurate estimate, see [13]- [17]. In [13], by exploiting the low-rank nature of the mmWave channels, we have proposed the TRICE framework, which formulates the CE in RIS-aided mmWave MIMO systems as a two-stage multidimensional sparse-recovery problem.…”
Section: Introductionmentioning
confidence: 99%